2010
DOI: 10.1002/lary.20803
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the safety of frontal sinus trephination

Abstract: Although the majority of patients have frontal sinuses deep enough to accommodate standard trephine instruments, surgeons should recognize that up to 15% of nonhypoplastic frontal sinuses may not be sufficiently deep at a given point to allow safe trephination without risking unintentional transgression of the posterior table. This study suggests that trephination routinely carried out at a given predetermined distance from the midline may be an unsafe practice. Careful evaluation of the imaging is essential i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Lee et al reviewed computerized tomography (CT) of 200 patients. They were able to show the mean depth of frontal sinus at 5 mm, 10 mm, and 15 mm from midline to be 11.26 mm (range, 0–21.8 mm), 11.45 mm (range, 0–23.1 mm), and 11.48 mm (range, 0–28.1 mm), respectively . This study showed no statistical difference in frontal sinus depth measurements performed at 5 mm, 10 mm, and 15 mm from a midline passing through the crista galli.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…Lee et al reviewed computerized tomography (CT) of 200 patients. They were able to show the mean depth of frontal sinus at 5 mm, 10 mm, and 15 mm from midline to be 11.26 mm (range, 0–21.8 mm), 11.45 mm (range, 0–23.1 mm), and 11.48 mm (range, 0–28.1 mm), respectively . This study showed no statistical difference in frontal sinus depth measurements performed at 5 mm, 10 mm, and 15 mm from a midline passing through the crista galli.…”
Section: Resultsmentioning
confidence: 60%
“…This study showed no statistical difference in frontal sinus depth measurements performed at 5 mm, 10 mm, and 15 mm from a midline passing through the crista galli. They concluded that the sinus can be successfully trephined at 5 mm, 10 mm, or 15 mm in a majority of patients . Piltcher et al reviewed 69 CT scans similarly at measurements of 5 mm, 10 mm, and 15 mm from midline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional teaching recommends performing it close to the floor of the sinus about 1-1.5 cm from the midline wherein the depth of the frontal sinus is the greatest thus minimizing the risk of posterior table penetration. Lee et al [26] recently measured the depth of the frontal sinus at 0.5, 1.0 and 1.5 cm from the midline and found no statistically significant difference in measurements. Lee did find an increased risk of cross trephination when performed 0.5 cm from midline because of the variable location of the intersinus septum.…”
Section: Frontal Sinus Trephinationmentioning
confidence: 96%
“…For example, before performing the trephination, this technology can be used to identify the floor of the frontal sinus near its midline, where the posterior table is farthest away. 42 Other complications noted in large series detailing patients who underwent trephination revealed a small risk of facial cellulitis (2.1%-4.5%), as well the risk of uncommon sequelae of CSF leak and orbital complications. 39,[43][44][45] Although not commonly used anymore, the external frontoethmoidectomy is still being performed in some centers for select frontal, ethmoid, orbital, and skull base pathologies.…”
Section: External Approaches To Frontal Sinus Surgerymentioning
confidence: 97%